IMPLEMENTASI METODE SERVQUAL DALAM MENGUKUR TINGKAT KEPUASAN PASIEN TERHADAP KUALITAS PELAYANAN RAWAT JALAN : Studi Kasus: Puskesmas Maubesi - Salu, Yoana Fransiska De Cantal; Nababan, Darsono; Seran, Krisantus Jumarto Tey (Universitas Methodist Indonesia, 2023)
The service quality of a Community Health Center does have a great impact on the patients' satisfaction. The Maubesi Community Health Center is one of the health services centers in Maubesi Village which serves a number of six surrounding villages. Given that many patients are making use of this health center, the service quality of the medical staff is of course quite essential. Patients' satisfaction is the primary factor which becomes the image benchmark of a community health center. Up to now, patients' satisfaction is measured in the conventional way, namely by writing on papers. The use òf paper certainly makes it hectic when the time for data compilation and analysis processing is due. To overcome this problem, the researcher developed a website-based information system (SISKESAN) to measure patients' satisfaction level at Maubesi Community Health Center. SISKESAN was developed based on website, to make it easy whenever and wherever the data is to be accessed. The system employs Service Quality Method (Servqual) to measure patients' satisfaction level using hope and fact values. To set up this system the researcher made use of Waterfall Method known as measurable gradual stages. By implementing SISKESAN at Maubesi Community Health Center, the patients' satisfaction level becomes easier in measurement. Patients can easily access the website and fill in the questionnaires prepared in the system. The result can be straightly seen by the staff in charge and it will become the benchmark for future policy making.